PEMANFAATAN LEMPUNG DESA GEMA TERAKTIVASI H 2SO 4 UNTUK PENINGKATAN KUALITAS AIR GAMBUT - Vina Rotua; Akmal Muchtar; Halida Sophia (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The clay found in Gema  Village, Kampar  Regency, Riau  Province  contains  many minerals, such as montmorillonite but it has a low surface area so need to do activation. The activator used in this study was  H2SO4 0,5 M solution. The adsorbent  was characterized by XRD, SEM and FT-IR. Activated Gema clay (LGT) and  unactivated Gema clay (LGTT) were applied for  purification a  peat water  using batch method with the  variation of  time 30, 60, 90 and 120 minute  and  several of water parameters were analized, such as odor, colour, pH, turbidity, TSS, TDS, concentrations of iron (Fe) and efficiency  of decreasing  of  colour. All the results  were compared  to  PERMENKES RI No. 416/MENKES/PER/IX/1990 “Tentang Syarat-Syarat Dan Pengawasan Kualitas Air”.  Activated  clay  showed the  refined morfology and increased which  surface area from 10,5813  m2g-1 up to 15,3337  m2g-1.  The  result  showed  that the  adsorption  using activated Gema clay is better than  unactivated Gema clay  that is showed from removal efficiency percentage for all parameters. The longer  of adsorption time, that was so many adsorbate that was adsorbed by adsorbent.  The maximum time  of  adsorption  was 120 minute. The  removal efficiency percentage  for pH, turbidity, TSS, TDS and efficiency of decreasing  of  colour were 10,03%, 30,98%, 58,59%, 59,28% and 30,84%, respectively for activated Gema clay (LGT).  The statistic result showed that the variation of adsorption time affect all parameters that  was  analyzed based on the analysis of variance (ANOVA) and Duncan’s test at α = 0,05.